The grotesque in Western art and culture : the image at play - Connelly, Frances S., 1953- (Cambridge : Cambridge University Press, 2012)
"This book establishes a fresh and expansive view of the grotesque in Western art and culture, from 1500 to the present day. Following the non-linear evolution of the grotesque, Frances S. Connelly analyzes key works, situating them within their immediate social and cultural contexts, as well as their place in the historical tradition. By taking a long historical view, the book reveals the grotesque to be a complex and continuous tradition comprised of several distinct strands: the ornamental, the carnivalesque and caricatural, the traumatic, and the profound. The book articulates a model for understanding the grotesque as a rupture of cultural boundaries that compromises and contradicts accepted realities. Connelly demonstrates that the grotesque is more than a style, genre, or subject; it is a cultural phenomenon engaging the central concerns of the humanistic debate today. Hybrid, ambivalent, and changeful, the grotesque is a shaping force in the modern era"--
Machine generated contents note: 1. Introduction: entering the Spielraum; 2. Improvisation I: grottesche; 3. Improvisation II: arabesques; 4. Subversion: the carnivalesque body; 5. Trauma: the failure of representation; 6. Revelation: profound play.
Includes bibliographical references and index.
Keywords: Grotesque; Grotesque in art; LITERARY CRITICISM / General